Cultivating Affective Competence through Innovative Approaches in Islamic Religious Education - Aspuri; Mowafg Abrahem Masuwd (EDUCARE: Jurnal Ilmu Pendidikan, 2025)
This study aims to examine the implementation of an innovative approach in Islamic religious education learning as a strategy to foster students' affective competence. This study uses a qualitative approach with a case study type. Data were obtained through in-depth interviews, classroom observations, and documentation of student activities. The results of the study indicate that innovative approaches such as project-based learning, reflection through digital media, and social case discussions are effective in fostering values such as empathy, honesty, responsibility, and social awareness in students. The role of teachers as value facilitators greatly influences the success of affective internalization, which is also reflected in increased student participation in social and worship activities. Documentation shows a real behavioral transformation in the school environment. This study provides a theoretical implication to the development of experience-based and contextual affective education, as well as being a practical reference for Islamic religious education teachers in designing learning strategies that touch the emotional realm of students. In addition, this study expands the discourse on character education in the context of vocational schools, which has so far been under-touched in similar research.